Structure, wellspring or content? : a conceptual analysis of the notion of tacit knowledge in knowledge management theory - Maasdorp, Christiaan Hendrik (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2004.